The role of mixed Mycoplasma and Herpesvirus infections in case of skin lesions in children - H. O. Kuvardina; F. S. Kharlamova; I. V. Polesko; O. V. Shamsheva; O. S. Ostapuschenko (Детские инфекции (Москва))
Numerous literature data show the role of mycoplasma infection in the development of non-respiratory lesions of various organs and systems, including the skin. Herpesvirus and mycoplasma infections can trigger the development of immune-mediated inflammatory reactions of the skin and mucous membranes — erythema multiforme exudative, Stevens-Johnson syndrome, vesicular pustular dermatosis — Sneddon-Wilkinson syndrome, etc.In order to study the frequency and nature of skin lesions with mycoplasmosis combined with herpesvirus infection, 45 patients aged 3 to 15 years of life were observed. A comprehensive clinical and laboratory study revealed skin lesions in 27 patients associated with current mycoplasma and herpesvirus infections. Thus, multiforme exudative erythema in the small form variant was diagnosed in 13 patients, skin vasculitis in 4, hemorrhagic purpura in 3, urticaria rash in 3, erythema nodosum in 2, mucositis in 2 children. In 18 children, a combined mycoplasma and herpesvirus infection was established. In 9 children, a mono infection was detected (in 5 — herpes virus and in 4 — mycoplasma).All observed patients showed antibodies to smooth muscle antigens in titers from 1:80 to 1:160 (normal 1:40) and in the vast majority (in 24 patients) — antibodies to vascular endothelial antigens in titers from 1:80 to 1:320 (with the norm of 1:40). Compaction of the intima-media complex was detected in 6 patients with monoinfection and in 16 patients with co-infection, according to ultrasound duplex scanning of the vessels of the brachiocephalic department.Thus, for various immuno-inflammatory, allergic skin diseases, screening for infections, in particular, mycoplasma and herpesvirus, is necessary to optimize treatment.